The The Relationship Between The Implementation of Sanitation Hygiene and Attitude and Knowledge Factors of School Snack Vendors In Karanganyar Regency - Sheylla Yasmin Agnestya; Denny Saptono Fahrurodzi (Jurnal Kesehatan Metro Sai Wawai, 2026)
Food is a basic human need that not only serves as a source of nutrition but also has the potential to become a medium for the spread of pathogenic microbes if not managed properly. In Indonesia, street food is a popular choice for the public, but often does not meet food safety standards. Inadequate sanitation hygiene from the production process to serving can trigger serious health problems and even death. This study aims to identify and analyze factors that influence the implementation of sanitation hygiene among street food vendors, with a focus on the attitude and knowledge aspects of the vendors. The method used in this study was a quantitative approach with 146 respondents. Data were collected through questionnaires and analyzed using univariate and bivariate tests. The results of the Chi-Square test on the attitude variable showed a p-value of 0.120 and knowledge 0.137. Because this value is greater than 0.05, it can be concluded that there is no significant relationship between the attitude of vendors and the implementation of sanitation hygiene. Although the majority of vendors with poor sanitation hygiene practices have poor attitudes (56.2%), and their knowledge is also classified as poor (66.4%), attitude and knowledge are not the primary determinants of these practices.